Evaluasi Kinerja Sistem IoT Berbasis ESP32 dan MQTT untuk Pemantauan Kelembapan Ruangan - Brian Brilliant; Ferliana Rahmadani; Helsen -; M. Ilham Firmansyah; M. Riski Tri Saputra; Norick Christian Frey; Rafly Isfandyar Sopyan; Abdul Rahman (Universitas Multi Data Palembang, 2026)
This study evaluates the performance of an ESP32 and MQTT-based IoT system for real-time humidity monitoring and regulation within a container. The system is developed by integrating a DHT22 sensor, relay module, and exhaust fan. Using a quantitative approach, this research measures system performance parameters, including sampling interval, Packet Delivery Ratio (PDR), and latency. The test results show an average sampling interval of 20.16 seconds with a 0.8% deviation from the ideal value. The achieved PDR level is 99.2%, with an average system latency of 725 ms. Based on the test results, the exhaust fan is capable of automatically reducing humidity when the sensor detects values above the 65% set point. Overall, the system demonstrates good reliability in maintaining stable data transmission and providing rapid control responses via the Virtuino IoT interface.